A Clinical Audit for Compliance on the Innovated Radiographic Technique at a Radiologic Unit - S. Ismanto; C.H. Hassan (ASEAN Journal on Science and Technology for Development, 2016)
This study identifed X-ray laboratory users’ compliance with the innovated radiographic technique and evaluated it’s effectiveness in decreasing risks of repeating unnecessary X-ray exposure. The use of various steps in the standard operating procedures of radiography, proper radiographic technique and critique, practical protection measures, and radiographic positioning practice in X-ray laboratory at a private radiographic academy in Indonesia were audited. Thirty participants were used as the simple random sample. The demographic distribution was divided into, gender, nationality, and practical experience. Generally, out of 30 participants, 20 (67%) complied, and 10 (33%) did not. Radiograph image results showed that proper radiographic technique was effective in decreasing repetitive exposure among X-ray laboratory users.